2021
DOI: 10.1111/cns.13763
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances and perspectives of postoperative neurological disorders in the elderly surgical patients

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 157 publications
0
27
0
Order By: Relevance
“…This study used a machine learning algorithm to build a predictive model to predict the risk of POD in patients with degenerative spinal disorders, which could suggest appropriate preventive measures for patients at risk, particularly by intervening early and correcting abnormal levels of controllable risk factors, and following the multicomponent intervention guidelines to prevent delirium released by The Hospital Elder Life Program (HELP). 43 , 44 This has implications for the patient's physical and mental health after surgery, early recovery, and savings in healthcare costs and resources. Using machine learning technology to establish disease prediction and risk‐assessment models can help clinicians better identify the factors that truly affect the prevalence and pathophysiology of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…This study used a machine learning algorithm to build a predictive model to predict the risk of POD in patients with degenerative spinal disorders, which could suggest appropriate preventive measures for patients at risk, particularly by intervening early and correcting abnormal levels of controllable risk factors, and following the multicomponent intervention guidelines to prevent delirium released by The Hospital Elder Life Program (HELP). 43 , 44 This has implications for the patient's physical and mental health after surgery, early recovery, and savings in healthcare costs and resources. Using machine learning technology to establish disease prediction and risk‐assessment models can help clinicians better identify the factors that truly affect the prevalence and pathophysiology of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…However, many other relevant factors in the perioperative period deserve equal attention. Decreased cerebral oxygen levels, inadequate cerebral perfusion due to prolonged hypotension, excessive blood loss, duration of surgery, clinical history of cerebrovascular disease, and postoperative pain are all risk factors for the development of POCD [ 94 , 95 ]. These factors may differentially stimulate the release of cellular inflammatory factors and exacerbate oxidative stress damage.…”
Section: Association Of Ferroptosis With Perioperative Neurocognitive...mentioning
confidence: 99%
“…Postoperative cognitive dysfunction (POCD), a common complication of surgery and anesthesia, has been recognized as a new-onset cognitive impairment after any type of surgical intervention, including cardiac and non-cardiac surgery, especially in the geriatric population, which may persist for a few days, months, or even years [3,4]. POCD is broadly characterized by a series of alterations in neurocognitive conditions and behavior, including impaired memory, poor comprehension, and reduced attention [5]. Previous studies have revealed that the incidence of POCD in older individuals varies from 16.7 to 89% one week after surgery [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%